Design (P and O) for standalone PV system based on iraqi irradiance - Assistant Lecturer Basim Jabbar Majeed (Genius Journals, 2023)
Solar energy is one of the most important sources of renewable energy, and it is noted that due to future studies and programs that are presented in the production of electricity, its importance will increase, so it is a natural source in addition to providing economic consumption. . . A friend of the environment. Cost and reduce reliance on generators that rely on fossil fuels, oil, coal and natural gas to operate. It therefore reduces pollution from fuel combustion and greenhouse gas emissions such as waste emissions, including carbon dioxide . Through this research, the levels of solar radiation falling in Iraq will be studied at stations spread in the governorates (Baghdad, Wasit, Basra and Muthanna) and a design proposal will be proposed to take advantage of the largest amount of radiation available to feed a solar energy system separated from the national grid with a certain load (kW)
Keywords: Solar radiation; renewable energy; inverter